2021
DOI: 10.1002/adsu.202100256
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth and Activation of Ag/Ag2S Nanowire Clusters by H2S Plasma Treatment for Promoted Electrocatalytic CO2 Reduction

Abstract: Nonmetallic activation of metal electrodes is effective and universal to improve the catalytic activity for the CO2 reduction reaction. Here, selective electrocatalytic reduction of CO2 is performed on a plasma‐activated Ag/Ag2S catalyst for the first time. By a facile H2S plasma treatment on Ag foil and subsequent electrochemical prereduction, Ag/Ag2S nanowire clusters are obtained in situ with different sizes. High Faradaic efficiency for CO generation on Ag/Ag2S is shifted to a significantly lower overpoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Nowadays, few studies on dealloying exist in the field of carbon dioxide electroreduction. 85–92 Yang et al 85 proposed an air calcination strategy for enriching the In–O content on the catalytic surfaces of In-based electrocatalysts. After the in situ electrochemical reconstruction (dealloying) process, the “skin” structured AC–In@InO x –CNT catalyst with enriched surface In–O content is formed.…”
Section: Dealloying Methods For Energy-conversion Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, few studies on dealloying exist in the field of carbon dioxide electroreduction. 85–92 Yang et al 85 proposed an air calcination strategy for enriching the In–O content on the catalytic surfaces of In-based electrocatalysts. After the in situ electrochemical reconstruction (dealloying) process, the “skin” structured AC–In@InO x –CNT catalyst with enriched surface In–O content is formed.…”
Section: Dealloying Methods For Energy-conversion Electrocatalysismentioning
confidence: 99%
“…The In–O enriched electrocatalyst exhibits significantly improved CO 2 RR activity, and the highest faradaic efficiency (FE) toward formate could reach 94 ± 1% with the partial current density of formate reaching 32.6 mA cm −2 at −1.0 V ( vs. RHE). Yang et al 86 first reported in situ on Ag foil using a facile plasma vulcanization treatment. After electrochemical prereduction, the electrodes possessed a structure of nanowire clusters with a significantly enlarged specific surface area.…”
Section: Dealloying Methods For Energy-conversion Electrocatalysismentioning
confidence: 99%
“…Introducing bimetallic structures into electrocatalysts is a new strategy. In electrocatalysts, the introduction of bimetallic materials can provide an interface effect different from that of a single metal. An interface effect refers to the interaction between two or more different components forming alloys or heterojunctions with similar structures in a kind of catalyst. And interface effects also play a crucial role in the application of electrocatalysts.…”
Section: Working Mechanism and Classification Of 1d Nanomaterials For...mentioning
confidence: 99%
“…20−22 Previously, Ag sulfides have been developed and exhibit enhanced CO formation activity; however, they do not give higher selectivity due to the increased hydrogen evolution activity. 21,23,24 Besides, it was noticed that sulfur atoms in inorganic components (e.g., Ag 2 S) were thermodynamically unstable and readily escaped from the catalyst when a negative potential was applied. 24,25 In contrast, sulfurs in thiol ligands show high affinity toward noble-metal atoms, making them promising candidates for surface modification on Ag for the CO 2 R. 26 The positive effect of a thiol ligand for the CO 2 R on Ag has been observed elsewhere; 14,21 the physical and chemical states of these ligands on the Ag surface, the origin of the thiol ligand effect on CO formation, and the effect on the competing hydrogen evolution reaction (HER), however, remain inconclusive, which motivated us to further explore the effect of a thiol ligand for the CO 2 R on Ag.…”
Section: Introductionmentioning
confidence: 99%
“…21,23,24 Besides, it was noticed that sulfur atoms in inorganic components (e.g., Ag 2 S) were thermodynamically unstable and readily escaped from the catalyst when a negative potential was applied. 24,25 In contrast, sulfurs in thiol ligands show high affinity toward noble-metal atoms, making them promising candidates for surface modification on Ag for the CO 2 R. 26 The positive effect of a thiol ligand for the CO 2 R on Ag has been observed elsewhere; 14,21 the physical and chemical states of these ligands on the Ag surface, the origin of the thiol ligand effect on CO formation, and the effect on the competing hydrogen evolution reaction (HER), however, remain inconclusive, which motivated us to further explore the effect of a thiol ligand for the CO 2 R on Ag. Herein, we first modified a polycrystalline Ag foil using a few different thiol ligands (simply by infiltration) and subsequently evaluated their CO 2 R performance, respectively (Figure 1 and Figure S1 and Table S1).…”
Section: Introductionmentioning
confidence: 99%